Serum Leptin levels in newly diagnosed Epileptic Patients - Sajida Parveen,; Zeba Haque,; Muhammad Ahsan,; Jawwad-us- Salam Khan,; Sidra Zaheer,; Syeda Samira Azim, (Journal of the Pakistan Medical Association, 2024)
Objective: To compare leptin levels in newly-diagnosed treatment-naive epileptic patients and healthy controls. Method: This case-control study was conducted from January 10 to September 15, 2022, at the Dow University of Health Sciences, Karachi, and comprised newly-diagnosed epileptic patients age 12-35years who had no comorbidity. The subjects were enrolled from the Neurology out-patient department of Civil Hospital, Karachi. Healthy individuals matched for age, gender and body mass index were also enrolled as controls. Blood samples were collected between 8am and 10am for the evaluation of serum leptin levels using enzyme-linked immunosorbent assay. Data was analysed using SPSS 26. Results: Of the 100 subjects, 64(64%) were males and 36(36%) were females. There were 50(50%) cases with mean age 19.34±5.65 years, and 50(50%) controls with mean age 19.76±5.67 (p=0.614). 100% of 50 individuals in control group did not have any family history of epilepsy,while 18% of cases (9) reported a positive family history. Mean leptin level in cases was 31.03±19.37 compared to 5.25±4.03 in the controls (p<0.05). Conclusion: Serum leptin levels were elevated in newly-diagnosed epileptic patients compared to healthy controls. Key Words: Epilepsy, Leptin, Leptin resistance.